Tibetan medicine Si-Wei-Qiang-Wei Powder ameliorates cholecystitis via inhibiting the production of pro-inflammatory cytokines and regulating the MAPK signaling pathway. (1st March 2023) - Zheng, Zhe; Xiong, Hui; Zhao, Zhongqiu; Zhou, Keli; Fu, Miao; Liu, Xinqiao; Mei, Zhinan
Abstract: Ethnopharmacological relevance: Si-Wei-Qiang-Wei Powder (SWQ) is a formulated traditional Tibetan medicine preparation that has been used clinically to treat liver and gallbladder diseases for centuries. Previous work has confirmed its clinical effectiveness, however, the specific mechanism of SWQ is still unknown. Aim of the study : This study aims to explore the anti-inflammatory effect of SWQ on cholecystitis and its possible mechanism. Materials and methods: The main chemical components of SWQ were analyzed by HPLC. The network pharmacology database was used to screen and construct the network of the main components and molecular targets of SWQ, and to predict the molecular pathways of its core targets. Cholecystitis guinea pig model and LPS stimulated cultured human gallbladder epithelial cells (HGBEC) were used, as in vivo and in vitro methods respectively, to study the anti-cholecystitis activity of SWQ. Specifically, gallbladder wall thickness, hematoxylin-eosin (H&E) staining, and liver function indexes were used to evaluate the anti-inflammatory activities of SWQ in cholecystitis; qRT-PCR and ELISA were used to detect the changes of the production of inflammatory cytokines; Western blot analysis was used to analyze the effects of SWQ on phosphorylation of P38, ERK1/2, JNK and AKT. Results: SWQ decreased the indexes of ALT, AST, TBA, CHOL, DBIL in serum and TBIL, TC and Ca 2+ in bile, and alleviated the wall thickness of gallbladder and hepatobiliary fibrosis in LCA-induced guinea pigs. In addition, SWQ attenuated the expression and production of TNF-α, IL-6, IL-1β, COX-2 both in liver and gallbladder. Moreover, SWQ reversed the up-regulation of p-P38, p-ERK1/2, and p-JNK in animals with cholecystitis and LPS-induced HGBEC. Furthermore, mechanistic studies indicated that SWQ inhibited the activation of ERK1/2, thereby decreasing the expression of TNF-α, IL-6, IL-1β and phosphorylation P38 and JNK. Conclusion: In summary, our research showed that SWQ relieves gallbladder inflammation by inhibiting the MAPK pathway. Graphical abstract: Image 1 Highlights: The drug components, theapeutic targets or signaling pathways of SWQ were clarified. SWQ inhibits cholecystitis via reversing the histological and biochemical changes. SWQ plays anti-inflammation by reducing the production of IL-1β, IL-6 and TNF-α. SWQ plays its anti-inflammatory effects by regulating MAPKs signaling pathway.